Should central banks' mandate be revised? - Yannis Stournaras (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
This paper revisits the evolving mandates of central banks in light of recent economic disruptions and structural shifts. Drawing on historical lessons from the Great Inflation and the Global Financial Crisis, it highlights the importance of price stability and central bank independence as foundational principles. The analysis focuses on the European Central Bank's (ECB) updated monetary policy strategy, emphasizing its mediumterm orientation, symmetric inflation target, and enhanced responsiveness to uncertainty. The paper also explores the broader role of central banks in supporting financial stability and addressing emerging challenges such as climate risk, digitalization, and geopolitical fragmentation. It argues that while central banks must remain anchored in their primary objective of price stability, their mandates should adapt to reinforce resilience and support sustainable growth. The conclusion calls for deeper institutional integration in the euro area to amplify the effectiveness of monetary policy and strengthen the international role of the euro.
Keywords: E52; E58; E61; 330; Central Bank Mandates; Price Stability; Monetary Policy Strategy; Financial Stability; Institutional Integration in the Euro Area